The Correlation Between Busulfan Exposure and Clinical Outcomes in Chinese Pediatric Patients: A Population Pharmacokinetic Study - Du, Xiaohuan; Huang, Chenrong; Xue, Ling; Jiao, Zheng; Zhu, Min; Li, Jie; Lu, Jun; Xiao, Peifang; Zhou, Xuemei; Mao, Chenmei; Zhu, Zengyan; Dong, Ji; et al. (Frontiers in Pharmacology, 2022)
Aims: The aims of the study were to 1) establish a population pharmacokinetic (Pop-PK) model for busulfan in Chinese pediatric patients undergoing hematopoietic stem cell transplantation (HSCT) and then estimate busulfan exposure and 2) explore the association between busulfan exposure and clinical outcomes. Methods: A total of 128 patients with 467 busulfan concentrations were obtained for Pop-PK modeling using nonlinear mixed effect model (NONMEM) software. Sixty-three patients who received the 16-dose busulfan conditioning regimen were enrolled to explore the correlations between clinical outcomes and the busulfan area under the concentration–time curve (AUC) using the Cox proportional hazards regression model, Kaplan–Meier method and logistic regression. Results: The typical values for clearance (CL) and distribution volume (V) of busulfan were 7.71 L h−1 and 42.4 L, respectively. The allometric normal fat mass (NFM) and maturation function (Fmat) can be used to describe the variability in CL, and the fat-free mass (FFM) can be used to describe the variability in V. Patients with AUCs of 950–1,600 µM × min had 83.7% (95% CI: 73.3–95.5) event-free survival (EFS) compared with 55.0% (95% CI: 37.0–81.8) for patients with low or high exposure (p = 0.024). The logistic regression analysis results showed no association between transplant-related toxicities and the busulfan AUC (p > 0.05). Conclusions: The variability in busulfan CL was related to the NFM and Fmat, while busulfan V was related to the FFM. Preliminary analysis results suggested that a busulfan AUC of 950–1,600 µM × min was associated with better EFS in children receiving the 16-dose busulfan regimen.